First Records of Scolebythidae and Chrysididae (Hymenoptera, Chrysidoidea) in Rovno Amber - Perkovsky, E.E.; Rasnitsyn, A.P. (Вестник зоологии, 2013)
Recorded from the Late Eocene Rovno amber (Ukraine) are above 300 families of Arthropoda. One hundred, seventy-four new species, 35 new genera and one new tribe have been described there in 45 families, including 42 species, 9 genera and one tribe of Hymenoptera. The first record of Scolebythidae is documented herein along with more detail information about Chrysididae which was only mentioned there before. Chrysidids are diverse and not very rare in the Rovno amber: four known inclusions represent at least three species in two genera. This makes a contrast with the Baltic amber: of 34 specimens known to Brues (1933), 30 represent only two species. Genera Pristapenesia Brues, Palaeobethylus Brues and Palaeobethyloides Brues and species Palaeobethylus politus Brues and Pristapenesia primaeva Brues, previously known in Baltic amber only, are recorded in Rovno amber as well.